STRATEGI KOMUNIKASI KEHUMASAN DALAM MEMBANGUN CITRA DI UNIVERSITAS MUHAMMADIYAH PALANGKARAYA - Rosmilawati, Srie; Eurotama, Rumbaka Fachrizal (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Public Relations is the spearhead of an agency/institution, to manage a positive image and is able to create a conducive atmosphere and harmonious relations from each element of the relevant agency/institution. UMPR Public Relations, which in carrying out its main duties and functions, has a public relations communication strategy in building its image. By building a good image, prospective applicants will be interested in continuing their studies at UMPR. But in fact for students in Palangka Raya City, UMPR is only used as a last resort when they want to continue their studies. Therefore, further studies are needed regarding the public relations communication strategy that has been implemented by the UMPR Public Relations so far. The method used is descriptive qualitative with data collection techniques namely observation, interviews, documentation and literature to describe the Public Relations communication strategy in building the image of Muhammadiyah University of Palangkaraya. Based on the research results, it was found that from several series of public relations communication strategies, UMPR Public Relations makes social media the most effective method and media in building an image at this time, because it can reach all levels of society. However, in reality on the ground, the strategy that has been implemented has not fully reached the audience, especially for prospective applicants. There are still a number of things that need to be improved so that the public relations communication strategy can be even better at building an image. More able to embrace all levels and throw away the public opinion.